URLs in Their Native Language: Opinions of Arab Users of the Internet - Moukdad, Haidar (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Contributions to a BBC news forum by 140 Arab listeners on "URLs in Arabic for the First Time" were analyzed. The analysis identified a wide range of views on the usefulness of Arabic URLs and showed a general uneasiness towards changing the familiar way of browsing and accessing Internet resources. Cette communication repose sur l'analyse des contributions de 140 auditeurs arabes à un forum de nouvelles de la BBC intitulé « URLs in Arabic for the First Time ». L'analyse démontre une grande variation de l'opinion sur l'utilité des URL en arabe ainsi qu'un malaise généralisé à l'idée de changer un mode de navigation et d'accès aux ressources internet familier.